Society and politics in an Ottoman town : 'Ayntāb in the 17th century - Canbakal, Hülya. (The Ottoman Empire and its heritage, 2007)
This book deals with a provincial town attending to its day-to-day business against the backdrop of an exacting war fought far afield against the Habsburgs (1683-99). The dynamics of long-term economic growth were temporarily disturbed by the wartime economy while realignment in center-periphery relations affected the local power structure and practices of status management. Meanwhile, the local elite continued to dominate public life, hence the lives of commoners. This study opens a window onto this world through a close examination of the court records of the town.